Intergovernmental fiscal relations and macroeconomic management in large countries - Gupta, S. P. Dr; Knight, Peter T.; Wen, Yin-Kann, 1943- (Allied Publishers, 1994)
Papers presented at the Senior Policy Seminar on Intergovernmental Fiscal Relations and Macroeconomic Management in Large Countries, held in New Delhi, February 26-28, 1991.